Mitochondria Regulate the Ca(2+)–Exocytosis Relationship of Bovine Adrenal Chromaffin Cells - Giovannucci, David R. (J Neurosci, 1999)
The present study expands the contemporary view of mitochondria as important participants in cellular Ca(2+) dynamics and provides evidence that mitochondria regulate the supply of release-competent secretory granules. Using pharmacological probes to inhibit mitochondrial Ca(2+) import, the ability of mitochondria to modulate secretory activity in single, patch-clamped bovine chromaffin cells was examined by simultaneously monitoring rapid changes in membrane surface area (ΔC(m)) and cytosolic Ca(2+) levels ([Ca(2+)](c)). Repetitive step depolarizations or action potential waveforms were found to raise the [Ca(2+)](c) of chromaffin cells into the 1 μm to tens of micromolar range. Inhibiting mitochondria by treatment with carbonyl cyanidep-(trifuoro-methoxy)phenylhydrazone, antimycin–oligomycin, or ruthenium red revealed that mitochondria are a prominent component for the clearance of Ca(2+) that entered via voltage-activated Ca(2+) channels. Disruption of cellular Ca(2+) homeostasis by poisoning mitochondria enhanced the secretory responsiveness of chromaffin cells by increasing the amplitude of the transient rise and the time course of recovery to baseline of the evoked Δ[Ca(2+)](c). The enhancement of the secretory response was represented by significant deviation of the Ca(2+)–exocytosis relationship from a standard relationship that equates Ca(2+) influx and ΔC(m). Thus, mitochondria would play a critical role in the control of secretory activity in chromaffin cells that undergo tonic or repetitive depolarizing activity, likely by limiting the Ca(2+)-dependent activation of specific proteins that recruit or prime secretory granules for exocytosis.